Spatial and temporal analysis of visceral leishmaniasis in the State of São Paulo in 1970 to 2014: risk areas increase over time (Research, Society and Development, 2020)
Nowadays, in Brazil, visceral leishmaniasis (VL) is classified as a re-emerging disease, in a clear process of epidemiological transition, along with an increased incidence in endemic areas, and present in four of the five regions of the country. Therefore, this essay aims to analyze the evolution and spatial distribution of VL in São Paulo, since its first record until the year 2014, in order to provide information for public health authorities to improve the control program. By means of an ecological and descriptive study, secondary data obtained from the Centro de Vigilância Epidemológica (CVE) and the Superintendência de Controle de Endemias (SUCEN) of São Paulo were analyzed and treated in a geographic information system (ArcGIS 10.1), with confection distribution maps. It was observed that there are two distinct patterns of distribution of LV in São Paulo: one in the western region, defined by the occurrence of human cases, high prevalence of canine cases and a greater number of municipalities where sand fly is present; the other, represented by the eastern region, characterized by the absence of reporting human cases, even where the sand flies and canine cases are present. It follows that western expansion of canine and human cases following the same expansion route as the vector is not a coincidence, since the phlebotomine sandflies records precede the notifications of the disease in dogs and subsequently in humans. The research is the basis for future studies and provides subsidies for actions of the State Control Program. It is suggested that there is a continuous survey of the presence vector and serological monitoring of dogs as well as education of the population so that it is receptive to euthanasia dogs in the positive cases, since in relation to the vector cycle, nothing can be done.